2012
DOI: 10.1108/02621711211219086
|View full text |Cite
|
Sign up to set email alerts
|

Visionary leadership in business schools: an institutional framework

Abstract: PurposeRecent decades have seen a change in the environment of business schools. These changes place great responsibility on deans as the leaders of schools to act. To date, there has been a dearth of literature dealing specifically with visionary responses on the part of the deans of business schools to those changes in the institutional environment. The purpose of this paper is to address the most recent institutional pressures in the business education field and present a framework linking it to the visiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Although the extant literature on business schools discusses a number of issues and challenges related to business school management (Bedeian, 2002;Davies and Thomas, 2009;Almog-Bareket, 2012;Thomas et al, 2014), few of them acknowledge the significant variation among the world's 14,000 business schools. In fact, research on the corporatization of business schools tends to focus on the 1,000 best-known, typically Western-based institutions while ignoring the diversity of the remaining majority (Alajoutsijärvi et al, 2013;Alajoutsijärvi et al, 2014).…”
Section: "The Dean's Squeeze Is a Fascinating 'Framing' Phenomenon Cmentioning
confidence: 99%
“…Although the extant literature on business schools discusses a number of issues and challenges related to business school management (Bedeian, 2002;Davies and Thomas, 2009;Almog-Bareket, 2012;Thomas et al, 2014), few of them acknowledge the significant variation among the world's 14,000 business schools. In fact, research on the corporatization of business schools tends to focus on the 1,000 best-known, typically Western-based institutions while ignoring the diversity of the remaining majority (Alajoutsijärvi et al, 2013;Alajoutsijärvi et al, 2014).…”
Section: "The Dean's Squeeze Is a Fascinating 'Framing' Phenomenon Cmentioning
confidence: 99%
“…Furthermore Barbara Brown (1998) said the visionary leader should have ten competencies to have, namely: (1) visualizing, the visionary leader should have a clear picture of what to accomplish and have a target that Obviously when it will be achieved, (2) futuristic thinking, the visionary leader thinks where the business position is at the moment and thinks the desired position in the future dating, (3) showing foresight, the visionary leader is a planner that can Estimate the future by considering what it wants to do and consider the technologies, procedures, organizations and other factors that affect the plan, (4) proactive planning, setting goals and strategies that are specific to achieving Such targets, visionary leaders can anticipate or consider potential obstacles and develop alternative plans to overcome obstacles, (5) Creative thinking, face the challenges of visionary leaders trying to find alternatives A new exit concerning issues, opportunities and problems, (6) Taking risks, dare to take risks and consider failures as an opportunity not a failure, (7) Process alignment. Aligning the process by knowing how to connect its own goals to the organization's goals, and aligning the tasks and work of each department across the organization, (8) The coalition building, building in order to achieve the self-target, he must create a harmonious relationship both inside and outside the organization and actively seeking opportunities to cooperate with a wide range of individuals, departments and specific classes, (9) Continuous learning, can Regularly be taking part in training and other types of development, both inside and outside the organization, it can test any interaction, negative or positive, to study the situation and be able to pursue opportunities to cooperate and take part in projects that can expand knowledge, giving challenges of thinking and developing imagination.…”
Section: Visionary Leadershipmentioning
confidence: 99%
“…Tony Manning and Bob Robertson (2002) revealed that it takes leadership more than just visionary leadership to face various situations in the face of change (Manning & Robertson, 2002). Granit Almog- Bareket (2012) found that strong visionary leadership in between is necessary to produce a unique identity and reputation of the organization (Almog- Bareket, 2012). Sonny N and Bill Richardson (1996) found that the main visionary transformer as the type of leadership needed to achieve success through strategic change (Nwankwo & Richardson, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Positive affects in terms of readiness for change and progress require vision to be effectively transferred (Kantabutra, 2010;Haque, TitiAmayah, & Liu, 2016), meanwhile collective vision also advances service job satisfaction and efforts (Testa, 1999). Due to the fact that leaders are responsible for creating and communicating organizational vision (Nanus 1992, in Almog-Bareket, 2012, personal vision is a source for developing organizational vision (Crossan et al, 2008, in Yoeli & Berkovich, 2010). An individual's enthusiasm, commitment and vision creating skills are required to implement change (Atkinson, 1999), consequently business students need to have vision crafting knowledge and skills required.…”
Section: Theoretical Overviewmentioning
confidence: 99%
“…Term vision derives from Latin and stands for »to see« (Almog-Bareket, 2012). Vision shows direction, articulates a sense of purpose, clarifies a set of ideals, as well as defines uniqueness (Berson, Shamir, Avolio, & Popper, 2001).…”
Section: Theoretical Overviewmentioning
confidence: 99%